Navigating Excellence: Optimizing Academic Risk Management through Strategic Planning in Private Universities - Nur Agus Salim; Lisa Handayani; Eka Selvi Handayani; Ratna Khairunnisa; Siska Oktaviani (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
Private universities face various challenges and risks in managing operations and achieving strategic goals. Therefore, strategic planning is crucial in risk management to enhance the quality of education. This study aims to analyze and implement strategic risk management plans at private universities. The research methods used include literature reviews to comprehend the fundamental concepts of risk management and strategic planning, along with case studies from several private universities that have successfully implemented strategic risk management planning. The results indicate that the integration of strategic planning and risk management plays a pivotal role in enhancing the resilience and performance of private universities. The implementation of strategic risk management plans in private universities involves specific steps such as risk identification, risk assessment, mitigation strategy development, and continuous monitoring. The participation of all stakeholders is also a crucial factor in the success of this implementation. This study presents a model for implementing strategic risk management plans that can be adopted by other private universities. The findings of this study are anticipated to offer practical guidance for educational institutions to enhance the effectiveness of risk management and better accomplish their strategic objectives.